Pertumbuhan, Hasil dan Kandungan Flavonoid Tiga Varietas Bawang Merah yang Dipengaruhi oleh Berbagai Dosis Pupuk K₂SO₄ pada Budidaya Terapung Rakit Bambu - Putri Lia Ananda; Susilawati Susilawati; Fitra Gustiar (Ranah Research : Journal of Multidisciplinary Research and Development, 2026)
Shallots (Allium ascalonicum L.) are one of the horticultural commodities that are widely consumed and contain several active chemical compounds that function as antioxidants such as flavonoids. This study aims to determine the growth and yield of various varieties of shallots (Allium ascalonicum L.) which are affected by the application of K₂SO₄ fertilizer in floating cultivation. The study was conducted at the research reservoir of the Faculty of Agriculture, Sriwijaya University located in South Indralaya District, Ogan Ilir Regency, South Sumatra Province. The method used in this study is a Factorial Randomized Block Design (RAKF) consisting of 2 factors, the first factor is the K2SO4 fertilizer factor consisting of 4 levels, namely: P0 (Control), P1 (30 kg/ha), P2 (60 kg/ha), P3 (90 kg/ha) and the second factor is the shallot plant variety factor consisting of 3 levels, namely: A1 (Bauji Variety), A2 (Bima Brebes Variety), A3 (Tajuk Variety). The parameters observed include: leaf length, leaf greenness, number of tillers and tuber dry weight. Application of K₂SO₄ fertilizer affects leaf length at 2 WAP, leaf greenness from 5 WAP to 7 WAP with the optimal dose of 90 kg/ha and the Bima Brebes variety produces the best variable in the number of tillers of 5.39 clumps, the Bauji variety produces the best tuber dry weight of 20.40 g/plant and the Tajuk variety produces the best variable in the number of leaves 20.21 strands, leaf length 41.45 cm, SPAD value of leaf greenness 45.62 and Flavonoid content 2.81 mg/L.